A Pediatric Transgender Medicine Curriculum for Multidisciplinary Trainees - Stanley R. Vance; Sara M. Buckelew; Brian Dentoni-Lasofsky; Elizabeth Ozer; Madeline B. Deutsch; Matthew Meyers (Association of American Medical Colleges, 2020)
Introduction While pediatricians should receive training in the care of transgender youth, a paucity of formal educational curricula have been developed to train learners to care for this vulnerable population. Methods We developed a curriculum including six online modules and an in-person afternoon session observing clinic visits in a pediatric gender clinic. Learners-fourth-year medical students, interns, and nurse practitioner trainees-received protected time during an adolescent medicine rotation to complete the online modules (total duration: 77 minutes). For 20 learners, we assessed the impact of the entire curriculum-online modules and in-person observation-on self-perceived knowledge of considerations for transgender youth. For 31 learners, we assessed the effect of the online modules alone on knowledge and self-efficacy. Descriptive analyses illustrated changes in educational domains by learner group. Results On evaluations of the entire curriculum (modules and observation), median self-perceived knowledge scores (1 = not at all knowledgeable/aware, 5 = extremely knowledgeable/aware) increased within learner groups: pediatric interns (from 2.3 to 4.0), nurse practitioner trainees (from 2.9 to 4.7), fourth-year medical students (from 3.3 to 4.9), and psychiatry interns (from 2.8 to 4.4). Assessment of learners completing only the online modules demonstrated increases in median knowledge and self-efficacy scores within learner groups. All learner groups highly valued the curriculum. Discussion Our curriculum for multidisciplinary learners in the care of transgender youth was successful and well received. Increasing learner knowledge and self-efficacy is an important step towards skill development in patient care for the transgender youth population.